1998
DOI: 10.1161/01.atv.18.3.466
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ApoE Content on Receptor Binding of Large, Buoyant LDL in Subjects With Different LDL Subclass Phenotypes

Abstract: Abstract-We investigated the influence of apolipoprotein (apo) E-containing particles on LDL receptor binding of large, buoyant LDL subfractions (LDL I) from subjects with predominantly large (phenotype A) and small (phenotype B) LDL particles. Direct binding by human fibroblast LDL receptors was tested at 4°C before and after removal of apoE-containing particles by immunoaffinity chromatography. The binding affinity of total LDL I in phenotype B was greater than that in phenotype A (Kd of 1.83Ϯ0.3 and 3.43Ϯ0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…ApoE is mainly expressed in astrocytes and microglia and appears as three major isoforms, ApoE2, ApoE3, and ApoE4, of which ApoE4 is the strongest genetic risk factor for AD (Stone et al, 1997;Ito et al, 2005;Vance and Hayashi, 2010;Chung et al, 2016;Liu et al, 2017;Montoliu-Gaya et al, 2018;Tulloch et al, 2018). ApoE4 demonstrates a lower affinity for lipids than ApoE2 and ApoE3, limiting CNS transport of lipids needed for neuronal remodeling and repair (Bradley and Gianturco, 1986;Barbagallo et al, 1998;Li et al, 2002;Frieden et al, 2017). Furthermore, levels of ApoE LDL receptors directly correlate with Aβ clearance, and promoting…”
Section: Contribution Of Lipoproteins To Ad Pathologymentioning
confidence: 99%
“…ApoE is mainly expressed in astrocytes and microglia and appears as three major isoforms, ApoE2, ApoE3, and ApoE4, of which ApoE4 is the strongest genetic risk factor for AD (Stone et al, 1997;Ito et al, 2005;Vance and Hayashi, 2010;Chung et al, 2016;Liu et al, 2017;Montoliu-Gaya et al, 2018;Tulloch et al, 2018). ApoE4 demonstrates a lower affinity for lipids than ApoE2 and ApoE3, limiting CNS transport of lipids needed for neuronal remodeling and repair (Bradley and Gianturco, 1986;Barbagallo et al, 1998;Li et al, 2002;Frieden et al, 2017). Furthermore, levels of ApoE LDL receptors directly correlate with Aβ clearance, and promoting…”
Section: Contribution Of Lipoproteins To Ad Pathologymentioning
confidence: 99%
“…However, such model-based optimization of systemic lipid diagnostics requires extensive improvements of the core model presented in this paper. The most relevant extensions and refinements necessary to increase the physiological reliability of the model are as follows: (i) inclusion of apoA-II (P02652, ENSG00000158874) to allow for differentiation between LpA-I and LpA-I:A-II particles to better satisfy the differing metabolic behavior of several HDL sub-populations in normal and pathological conditions [25],[40]; (ii) inclusion of apoB-48 in addition to apoB-100 to model the metabolism of intestinal synthesized chylomicrons even with respect to postprandial hyperlipidemia [41],[42]; (iii) distinguishing between free cholesterol and cholesteryl ester and inclusion of the esterification process of free cholesterol by LCAT [43]; (iv) disaggregation of the model component variable F into apolipoproteins E and C and explicit consideration of the regulatory function of these isoforms (e.g., activating effect of apoC-I [P02654, ENSG00000130208] on LCAT [44], activation of LPL by apoC-II [P02655, ENSG00000213044] [26], influence on the LDL receptor binding by apoE [45], and the apoE-dependent alternative path for peripheral cholesterol [46]); (v) explicit incorporation of the phospholipid exchange mediated by the phospholipid transfer protein (PLTP; P55058, ENSG00000100979) playing a key role in the remodeling of HDL [47],[48]; and (vi) inclusion of other transporters and receptors involved either in the holoparticle uptake or in the uptake of individual lipoprotein components, e.g., SR-B1 (Q8WTV0, ENSG00000073060), ABCG1 (P45844, ENSG00000160179), and ABCG4 (Q9H172, ENSG00000172350) [49],[50].…”
Section: Discussionmentioning
confidence: 99%
“…40 Recent studies have also demonstrated an effect of apo E containing particles on LDL receptor binding of buoyant LDL, which differs between subjects with predominantly small or large LDL particles. 41 In the present study, we have examined the relationships between LDL and HDL particle sizes, determined aftergradient gel electrophoresis, and apo E phenotypes, in particular the possession of ⑀4 and ⑀2 alleles in control subjects and those with CHD. The role of plasma triglyceride in effecting such modulations has been determined, with particular attention to postprandial changes in HDL particles.…”
mentioning
confidence: 99%